Traumatic Axonal Injury: Mechanisms and Translational Opportunities. Issue 5 (May 2016) - Hill, Ciaran S.; Coleman, Michael P.; Menon, David K.
Abstract : Traumatic axonal injury (TAI) is an important pathoanatomical subgroup of traumatic brain injury (TBI) and a major driver of mortality and functional impairment. Experimental models have provided insights into the effects of mechanical deformation on the neuronal cytoskeleton and the subsequent processes that drive axonal injury. There is also increasing recognition that axonal or white matter loss may progress for years post-injury and represent one mechanistic framework for progressive neurodegeneration after TBI. Previous trials of novel therapies have failed to make an impact on clinical outcome, in both TBI in general and TAI in particular. Recent advances in understanding the cellular and molecular mechanisms of injury have the potential to translate into novel therapeutic targets. Trends: Multiple therapeutic targets are emerging that offer the potential to reduce secondary brain injury at a cellular level. These include cytoskeletal and membrane stabilisation, control of calcium flux and calpain activation, optimisation of cellular energetics, and modulation of the inflammatory response. Wallerian degeneration, as occurs following an axonal injury, is an active, cell-autonomous death pathway that involves failure of axonal transport to deliver key enzymes involved in NAD biosynthesis. Chronic microglial activation occurs following traumatic brain injury (TBI) and may persist for decades afterwards. This ongoing response has been linked to long-term neurodegeneration, particularly of white matter tracts. Phagoptosis is the process whereby physiologically stressed but otherwise viable neurons are phagocytosed by microglia in response to a range of eat-me signals induced by tissue injury.